TRIM21 modulates stability of pro-survival non-coding RNA vtRNA1-1 in human hepatocellular carcinoma cells. - EunBin Kong; Norbert Polacek (PLoS Genetics)
Recent studies expanded our knowledge of diverse pro-survival functions of short non-coding vault RNAs. One of the human vault RNA paralogs, vtRNA1-1, modulates several intracellular processes, including proliferation, apoptosis, autophagy, and drug resistance in various types of human cancer cells. However, protein interaction partners and mechanisms by which vtRNA1-1 levels are controlled within the cells remained elusive. Here, we describe a regulatory process for vtRNA1-1 stabilization mediated by the newly identified interacting proteins, TRIM21 and TRIM25, in human hepatocellular carcinoma (HCC) cells. Depleting TRIM21 or TRIM25 reduced the stability of vtRNA1-1 both in vivo and in vitro. We also identified the responsible sequence of vtRNA1-1 for the stability regulation by TRIM21 and TRIM25 and revealed another critical factor for vtRNA1-1 stability, an NSUN2-mediated methylation at C69 of vtRNA1-1. Consequently, our findings demonstrated that the TRIM proteins govern the stability of vtRNA1-1 depending on its methylation status in HCC cells. Since vtRNA1-1 is crucial for pro-survival characteristics in HCC cells, insight into vtRNA1-1 protein binding partners and the regulation of its stability can impact the development of new anticancer strategies.